BIOMEDICAL ENGINEERING - Sodikova Dilnavoz Kambaraliyevna (Web of Journals Publishing, 2023)
Biomedical engineering is a multidisciplinary field that merges principles of engineering, biology, and medicine to develop innovative solutions for healthcare challenges. This article provides a thorough examination of recent advancements in biomedical engineering, exploring key literature, methodologies employed, and the implications of these developments on patient care. The study aims to highlight the interdisciplinary nature of biomedical engineering and its role in shaping the future of healthcare.